EFFECT OF VISFATIN ON TESTICULAR STEROIDOGENESIS IN PURIFIED LEYDIG CELLS - Hameed, Waqas; Yousaf, Iftekhar; Latif, Rabia; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: Lower testosterone levels have been reported in men suffering from diabetes mellitus. Men with insulin resistance states such as obesity and type 2 diabetes mellitus have significantly lower testosterone levels than age-matched normal weight and non-diabetic controls. Adipose tissue secretes variety of adipokinesincluding adiponectin, resistin, visfatin, TNF-Î±. The study was designed to study the effect of visfatin on testicular steroidogenesis in purified Leydig cell in vitro. Methods: Leydig cells of Sprague Dawley rats were isolated and purified by Percoll. Cells were incubated for 3 hours with/without visfatin in the presence/absence of LH and intracellular signalling blockers including PKC blocker, PKA blocker and Raf1/Ras blocker. Cell culture extracts were stored at -80 „ƒ before analysis for levels of testosterone hormone by ELISA. Results: Visfatin increased testosterone production (p<0.001) from cultured Leydig cells. Raf1/Ras blocker decreased visfatin induced steroidogenesis (p<0.001). Conclusion: Visfatin increased testicular steroidogenesis from Leydig cells in vitro models and operates through variety of enzymes, but especially through Ras/Raf1 kinase enzymes. Keywords: Visfatin, adipocytokines, Leydig cells, testicular steroidogenesis